Pengaruh Intellectual Capital, Free Cash Flow dan Struktur Modal terhadap Kinerja Keuangan Perusahaan: Studi Empiris pada Perusahaan Manufaktur Terdaftar di Bursa Efek Indonesia (BEI) Periode 2019-2021 - Franiza, Widia; Taqwa, Salma (Universitas Negeri Padang, 2024)
This research aims to determine the influence of intellectual capital, free cash flow and capital structure on the company’s financial performance. The population used in this research is manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021. The sampling technique in this research used a purposive sampling technique, there were 54 companies used as samples. The data used in this research is secondary data. Data collection techniques using documentation methods on www.idx.co.id. The statistical method uses is multiple linear regression analysis. The research results show that intellectual capital and free cash flow have a significant positive effect on the company’s financial performance, while capital structure has a significant negative effect on the company’s financial performance.